A Novel Buffer Tank to Attenuate the Peak Flow of Runoff - Yinghong Qin; Zhengce Huang; Zebin Yu; Zhikui Liu; Lei Wang (Salehan Institute of Higher Education, 2019)
Impermeable pavements and roofs in urban areas convert most rainfall to runoff, which is commonly discharged to local sewers pipes and finally to the nearby streams and rivers. In case of heavy rain, the peak flow of runoff usually exceeds the carrying capacity of the local sewer pipes, leading to urban flooding. Traditional facilities, such as green roofs, permeable pavements, soakaways, rainwater tanks, rain barrels, and others reduce the runoff volume in case of a small rain but fail in case of a heavy rain. Here we propose a novel rainwater buffer tank to detain runoff from the nearby sealed surfaces in case of heavy rain and then to discharge rainwater from an orifice at the tank’s bottom. We found that considering a 100m2 rooftop with 0.80 runoff coefficient and a 10cm rainfall depth for an hour, a cubic tank with internal edge side of a square of 2 m attenuates the peak flow about 45%. To reduce a desirable peak flow, the outlet orifice of the buffer tank must be optimized according to site-specific conditions. The orifice can be set at an elevation from the tank’s bottom to create a dead storage for harvesting rainwater.